THE EFFECTIVENESS OF FAMILY EMPOWERMENT IN THE LATENT TB INFECTION TOWARDS TB PATIENTS’ OBEDIENCE AND CAREGIVER BURDEN - Puspa Wardhani; Kelana Kusuma Dharma; Susito Susito (Universitas Padjadjaran, 2021)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis, causing coughing, fever, and chest pain. There were 50 people suffering pulmonary TB In Public Health Center in Siantan Hilir Pontianak who must be treated immediately. Intervention is crucial because of many cases of TB recurrence. This study aimed to determine the effectiveness of family empowerment in latent screening for TB Infection based on WHO guidelines on the level of TB patient obedience and family burden. The research method was a quasi experimental study involving 36 people (family) of TB sufferers with consecutive sampling technique. As many as 18 people received empowerment (treatment) interventions, and 18 others were not treated. Before, they given informed consent in each group. The study was conducted for two months and have given three visits therapy during the study for the intervention group. The instruments used were Morisky Medication Obedience Scale-8 (MMAS-8) and Caregiver Burden Scale (CBS). The results showed that there were significant differences related to family empowerment in WHO-based latent screening on TB Infection in increasing patient obedience with p = 0,000 and for caregiver burden with p= 0,000 (p <0.005). It is expected by applying the family empowerment in screening could prevent and reduced the morbidity of TB sufferers. The family empowerment can increase the obedience of patients with pulmonary TB and reduce the burden on the family.